2018
DOI: 10.1021/acs.est.8b01604
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Network Analyses Reveal Mechanistic-Based Biomarkers of Endocrine Disruption in the Marine Mussel, Mytilus edulis

Abstract: Transcriptomics, high-throughput assays, and adverse outcome pathways (AOP) are promising approaches applied to toxicity monitoring in the 21st century, but development of these methods is challenging for nonmodel organisms and emerging contaminants. For example, Endocrine Disrupting Compounds (EDCs) may cause reproductive impairments and feminization of male bivalves; however, the mechanism linked to this adverse outcome is unknown. To develop mechanism-based biomarkers that may be linked through an AOP, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 95 publications
(152 reference statements)
2
24
0
Order By: Relevance
“…A review of research on the identification and functioning of invertebrate receptors and pathways, in comparison to those in their vertebrate counterparts can be found in Lafont & Mathieu (2007). More recently Blalock et al (2018) have reported evidence of a cholesterol side chain cleavage enzyme consistent with endogenous production of steroids and oestrogen signalling pathway, as a likely mechanism of action in mussels M. edulis exposed to 17-α-ethinylestradiol and 4-nonylphenol. A ligand-activated ER-like receptor has also been found in reproductive tissue of marine rotifers Brachionus manjavacas (Fontaneto, Giordani, Melone & Serra, 2007) which appears to bind human oestradiol and regulates reproductive output in females.…”
Section: Invertebratesmentioning
confidence: 99%
“…A review of research on the identification and functioning of invertebrate receptors and pathways, in comparison to those in their vertebrate counterparts can be found in Lafont & Mathieu (2007). More recently Blalock et al (2018) have reported evidence of a cholesterol side chain cleavage enzyme consistent with endogenous production of steroids and oestrogen signalling pathway, as a likely mechanism of action in mussels M. edulis exposed to 17-α-ethinylestradiol and 4-nonylphenol. A ligand-activated ER-like receptor has also been found in reproductive tissue of marine rotifers Brachionus manjavacas (Fontaneto, Giordani, Melone & Serra, 2007) which appears to bind human oestradiol and regulates reproductive output in females.…”
Section: Invertebratesmentioning
confidence: 99%
“…Presence of numerous contaminants from various (e.g., wastewater effluent, industrial wastewater discharge, oil and chemical spills, urban runoff, agricultural runoff) sources make the risk assessment and monitoring challenging. 17 High-throughput in vitro assays and AOP-based approach is promising for the assessment of health and ecotoxicological risks from exposure to pollutants and their mixtures. [17][18][19][20][21] Establishment of a quantitative AOP framework through integration of computational modeling with in-vitro assays would require identification and selection of relevant biomarkers from appropriate bioassays that link to risk assessment pathways and phenotypic impacts.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…17 High-throughput in vitro assays and AOP-based approach is promising for the assessment of health and ecotoxicological risks from exposure to pollutants and their mixtures. [17][18][19][20][21] Establishment of a quantitative AOP framework through integration of computational modeling with in-vitro assays would require identification and selection of relevant biomarkers from appropriate bioassays that link to risk assessment pathways and phenotypic impacts. 18,21,66 Current toxicomics approach still mostly rely on large number of redundant markers without pre-selection or ranking; 3,51,67 therefore, selection of relevant biomarkers with minimal redundancy would reduce the number of markers to be monitored and reduce the cost, time, and complexity of the toxicity risk monitoring.…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, toxicogenomics data mining and in silico techniques have been gradually developing as efficient approaches to speed up AOP development. Premier public resources (such as the Comparative Toxicogenomics Database (CTD), ToxCast, AOP Wiki database, etc.) can provide a chance to generate analytical toxic pathways. , Oki and Edwards generated multiple AOP predictions by evaluating the associations of chemical–gene–disease data in the CTD . Jeong et al developed AOPs using mammalian toxicity data obtained from ToxCast .…”
Section: Introductionmentioning
confidence: 99%